MODELLING AND SIMULATION OF A COMPANY INVENTORY USING ARENA SOFTWARE - Hairullidzam, Nursyafiqah; Ahmad Bareduan, Salleh (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Managing inventory is very important. When managing inventories, many kinds of businesses encounter various complex issues. Previous inventory management systems used simple mathematical equations to determine order amount and time to order. Some companies collect and store orders manually. Therefore, inventory management must be done only using the available options and capabilities. When a company's order volume increases, the system for collecting and delivering orders becomes complex and ineffective. At this point, Arena software is proposed in this study as a modern tool for helping the company in solving inventory-related problems. This study aims to build a model of the company inventory system using Arena Simulation Software and to provide the analysis of the simulation result related to the inventory system. The data used for this study were obtained from Bucky company, which is a company model by Kelton. This study used modules from the Blocks and Elements panels from Arena Software to build the simulation model with the capability to analyze the inventory management. The procedures include data gathering, model building, simulation, verification and validation and performance analysis. The model was verified by comparing the simulation result with the result from Kelton related to the values of daily holding cost, shortage cost, and ordering cost. The verification process showed that the model performed exactly the same as referenced model. A new model from small warehouse inventory was developed to test the capability of imitating a similar model analysis. The results showed that the value of crane utilization was 99.98%, average inventory level was 28.90, average total cost was $170.65 and 57 number of unfilled requests. This study can be used in the future to reduce total inventory expenses through simulation analysis, while also highlighting how simulation techniques can be effectively used to solve problems related to inventory management.